Application of Engineered Bacteriophage T7 in the Detection of Bacteria in Food Matrices - Wisuthiphaet, Nicharee; Yang, Xu; Young, Glenn M.; Nitin, Nitin (Frontiers in Microbiology, 2021)
Detection of pathogens in a food matrix is challenging due to various constraints including complexity and cost of sample preparation for microbial analysis from food samples, time period for the detection of pathogens and high cost and specialized resources required for advanced molecular assays. To address some of these key challenges, this study illustrates a simple and a rapid colorimetric detection of target bacteria in diverse food matrices, including fresh produce, without prior isolation of bacteria from a food matrix. This approach combines bacteriophage induced expression of an exogenous enzyme, alkaline phosphatase, specific colorimetric substrates that generate in-soluble color products and a simple filtration method to localize the generation of colored signal. Using this approach, this study demonstrates specific detection of inoculated E. coli in coconut water and baby spinach leaves. Without isolation of bacteria from the selected food matrices and using food sample size that is representative of industrial samples, the inoculated samples were added to the enrichment broth for a short period (5 hours) and incubated with an engineered bacteriophage T7 with phoA gene. The incubation period with the engineered phage was 30 min for liquid samples and 2 hours for fresh produce samples. The samples were then filtered through a 0.2-micron polycarbonate membrane and incubated with a colorimetric substrate, i.e., 5-bromo-4-chloro-3-indolyl phosphate (NBT/BCIP). This substrate forms a dark purple precipitate upon interactions with the released enzymes on a filter membrane. This approach successfully detected 10 CFU/ml of E. coli in coconut water and 102 CFU/g of E. coli on baby spinach leaves with 5 hours of enrichment. Success of this approach illustrates potential for detecting target bacteria in food systems using a simple visual assay and quantitative colorimetric measurements.